Truncal Instability and Titubation in Patients With Acute Encephalopathy With Reduced Subcortical Diffusion - Kawano, Go; Yae, Yukako; Sakata, Kensuke; Yokochi, Takaoki; Imagi, Toru; Ohbu, Keizo; Matsuishi, Toyojiro (Frontiers in Neurology, 2021)
The present retrospective study aimed to investigate the presence of truncal instability or titubation after the first seizure and second phase in patients with acute encephalopathy with reduced subcortical diffusion (AED). Of the 15 patients with AED who were admitted to our hospital for 3 years and 2 months and had reached developmental milestones for sitting before disease onset, six experienced moderate-to-severe truncal instability while sitting after the first seizure. These patients had a significantly longer first seizure duration and significantly lower GCS scores 12–24 h after the first seizure, as well as significantly higher Tada score and Creatinine and blood glucose levels than those with mild or no truncal instability while in a seated position after the first seizure. Three 1-year-old children with bilateral frontal lobe lesions, particularly in the bilateral prefrontal lobe regions, demonstrated truncal titubation, which has not previously been reported as a clinical feature of AED. Tada score reported to be a predictor of AED prognosis and truncal instability in the sitting position after the first seizure may represent disease severity, but not the specific lesions. Conversely, truncal titubation might be suggestive of bilateral frontal lobe lesions, particularly in patients without severe instability. Further studies on the role of bilateral prefrontal lobe lesions to truncal titubation in patients with AED using more objective evaluation methods, such as stabilometry, are necessary.